AKTUALISASI PENDIDIKAN KARAKTER DALAM PRAMUKA ANAK 5-6 TAHUN DI TK ISLAMIYAH PONTIANAK TENGGARA. - Sari, Kartika; Marmawi, Marmawi; Amalia, Annisa (Universitas Tanjungpura, 2024)
This study describes the actualization of character education in scouting activities for children aged 5-6 years at Kindergarten Islamiyah, Southeast Pontianak District. The research method used qualitative. The subjects study were 2 scout coaches. Data collection techniques used observation, interviews and documentation. Data analysis was carried out namely data collection, data reduction, data presentation and drawing conclusions. Data validity checking technique uses triangulation. The results of the study: 1. Actualization of self-loving character in scout activities, namely children participating in scout activities with full confidence and confidence. The activity marching and individual games to put water into the bottle. 2. Actualization of the character of loving others in scouting activities, namely the friendly attitude of children to each scout member and scout coach and respecting others manifested through marching activities, forming circles, holding each other, group games,singing while clapping. 3. Actualization of the character of loving the environment in scout activities, namely that children want to take part in scout activities in the field, protect the environment and care for the environment so that it is clean, comfortable and safe for children when carrying out scout activities. In conclusion: character education has been carried out well for children in Kindergarten Islamiyah,Southeast Pontianak through marching activities, playing, singing, clapping and activities related to the character of loving yourself, loving others and loving the environment. The suggestion: children should be more confident and carry out each activity independently.